VISUALISING CONFLICT: ANALYSING EDITORIAL CARTOONS ON THE ISRAELI-PALESTINIAN CONFLICT IN ŞALOM NEWSPAPER (Third Sector Social Economic Review, 2024)
This study analyses how the Israeli-Palestinian conflict was represented in the editorial cartoons produced by the Şalom newspaper following the intensification of the conflict between Israel and Gaza as of October 2023. The long-standing disputes between Israel and Palestine, which have their origins in the late 18th century and have not been resolved despite the involvement of numerous international countries, have recently assumed a new violent character. The military operations of Israel in Gaza resulted in significant civilian casualties, particularly among women and children, and sparked widespread protests and demonstrations around the world. The study uses multimodal discourse analysis to examine the symbolic, visual, metaphorical and textual aspects of these cartoons. It also considers the ownership structure and historical context of the newspaper Şalom. It finds that the editorial cartoons in Şalom highlight the human cost of the conflict and encourage readers to engage critically with the issues. The paper highlights that while the newspaper is critical of Israel's actions in Gaza in its cartoons, it avoids direct references to Hamas or the Palestinian resistance. This study illuminates how the media representations of conflict can be employed to shape public perception and discourse.
Keywords: Israeli-Palestinian conflict; Şalom; editorial cartoons; political cartoons; multimodal discourse analysis